VARIETAL RESISTANCE OF PEA TO POWDERY MILDEW - I.U. HAQ AND M. ASLAM, TARIQ MAHMOOD, I. AHMAD* (Indian Phytopathology, 2002)
Twenty three varieties of pea (Pisum satilium) were tested at National Agricultural Research Centre, Islamabad for their resistance against powdery mildew disease. Seventeen varieties, mostly prevailing ones, were found to be highly susceptible. Among the varieties supplied by FAO, Groch Szesciolygodniany was susceptible; Groch Benjaminek and Groch cud kehredonu were moderately resistant; and Groch Laser was found to be resistant.